2022
DOI: 10.3390/ijms23020955
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Changes in Protein Composition of Medial Prefrontal Cortex in Rats with Neuropathic Pain

Abstract: Chronic pain is associated with time-dependent structural and functional reorganization of the prefrontal cortex that may reflect adaptive pain compensatory and/or maladaptive pain-promoting mechanisms. However, the molecular underpinnings of these changes and whether there are time-dependent relationships to pain progression are not well characterized. In this study, we analyzed protein composition in the medial prefrontal cortex (mPFC) of rats at two timepoints after spinal nerve ligation (SNL) using two-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Analysis of the differences in translational and posttranslational modifications in the nervous system that occur after injury by SNI can help identify key biological markers of SNI that can be used as major molecular targets for drug therapy and improve the efficacy of SNI treatment (Niederberger and Geisslinger, 2008). A number of studies have been conducted using different animal models to simulate the onset of SNI and for the triggers of SNI (e.g., viruses (Wang et al, 2022c)), therapeutic agents (Chen et al, 2022b;Xiong et al, 2022), temporal changes (Ujcikova et al, 2022;Vergara et al, 2018). In contrast, the current study constructed ex vivo models of SNI using compressive injury and OGD induction and explored DEPs in SNI that suffered an injury based on label-free quantitative proteomics extraction and identification of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the differences in translational and posttranslational modifications in the nervous system that occur after injury by SNI can help identify key biological markers of SNI that can be used as major molecular targets for drug therapy and improve the efficacy of SNI treatment (Niederberger and Geisslinger, 2008). A number of studies have been conducted using different animal models to simulate the onset of SNI and for the triggers of SNI (e.g., viruses (Wang et al, 2022c)), therapeutic agents (Chen et al, 2022b;Xiong et al, 2022), temporal changes (Ujcikova et al, 2022;Vergara et al, 2018). In contrast, the current study constructed ex vivo models of SNI using compressive injury and OGD induction and explored DEPs in SNI that suffered an injury based on label-free quantitative proteomics extraction and identification of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The perception and transmission of pain is a complex phenomenon that depends on an extended network of different cortical brain regions, including the primary somatosensory cortex, prefrontal cortex, anterior cingulate cortex, insular cortex, and so on (Kuner & Kuner, 2021; Mouraux & Iannetti, 2018). Numerous studies have confirmed that the structural changes and functional changes in the above brain regions are closely associated with the presence of NeP (Kim, Kim, & Nabekura, 2017; Selvarajah et al, 2019; Ujcikova et al, 2022; Wang, Zhang, Wang, & Luo, 2021; Zhao et al, 2018). These changes mainly include the calcium activity of neurons, excitatory postsynaptic current (EPSC) frequency and amplitude, synaptic strength, intrinsic excitability, the turnover rate or density of dendritic spines, and brain oscillations, which can be recognized as biomarkers for NeP (Bak, Park, & Kim, 2021; Zhuo, 2020).…”
Section: Introductionmentioning
confidence: 90%
“…The perception and transmission of pain is a complex phenomenon that depends on an extended network of different cortical brain regions, including the primary somatosensory cortex, prefrontal cortex, anterior cingulate cortex, insular cortex, and so on Mouraux & Iannetti, 2018). Numerous studies have confirmed that the structural changes and functional changes in the above brain regions are closely associated with the presence of NeP (Kim, Kim, & Nabekura, 2017;Selvarajah et al, 2019;Ujcikova et al, 2022;Wang, Zhang, Wang, & Luo, 2021;Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It critically modulates the pain experience and a large number of comorbidities of painful disease are evoked by PFC changes, structural reorganization of neurons and glia, signal transduction, and cellular metabolism. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%